2021
DOI: 10.3389/fmed.2021.715294
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well-Being of Older Adults With Cognitive Deterioration During Quarantine: Preliminary Results From the GeroCovid Initiative

Abstract: Objectives: The spread of COVID-19 has undeniably unsettled the social, psychological and emotional life of the entire world population. Particular attention should be paid to older adults with dementia, given their vulnerability to emotional stressors. The aim of this retrospective study is to evaluate the impact of the first wave quarantine related to Covid-19 on psychological and affective well-being of older adults with mild/major neurocognitive disorders and of their caregivers.Methods: Data on participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 37 publications
(59 reference statements)
0
18
0
Order By: Relevance
“…This was attributed to older adults being at higher risk for severe disease, fear of the unknown, loss of friends and family, and restrictions to prevent the spread of the virus. Those with cognitive impairments and dementia also experienced symptoms of depression, stress, and had difficulty coping despite perceptions of reduced awareness (Coin et al, 2021; Murukesu et al, 2021). Although, Murukesu et al found that providing supportive services, counseling, and daily exercise were effective measures for promoting psychological well‐being among older adults, the reality was many of these resources were reduced during the pandemic due to insufficient staffing and funding to include socioeconomic and political barriers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This was attributed to older adults being at higher risk for severe disease, fear of the unknown, loss of friends and family, and restrictions to prevent the spread of the virus. Those with cognitive impairments and dementia also experienced symptoms of depression, stress, and had difficulty coping despite perceptions of reduced awareness (Coin et al, 2021; Murukesu et al, 2021). Although, Murukesu et al found that providing supportive services, counseling, and daily exercise were effective measures for promoting psychological well‐being among older adults, the reality was many of these resources were reduced during the pandemic due to insufficient staffing and funding to include socioeconomic and political barriers.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID‐19 pandemic is a global crisis; therefore available research provided a broad perspective on the well‐being of older adults from 13 different countries using a variety of research designs, methods, and measurements. The majority of studies recruited participants from sources such as community centers, geriatric organizations, physician practices, national databases, and social media with only three studies examining long‐term care residents (Coin et al, 2021; López et al, 2020; Matteucci, 2021). Two major themes from the literature review will be discussed which includes psychological well‐being and social well‐being along with various concepts associated with these themes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations